Strengthening Coastal Community Resilience through the Tsunami Ready Program in Padang City: English - Zahran Mabrukah Tomimi; Hendri Koeswara; Roni Ekha Putera; Ria Ariany; Medika Julian; Hanifa Azzahra (Warta Pengabdian Andalas, 2026)
This community service program aims to strengthen the resilience of coastal communities in Purus Village, Padang City, a high-risk tsunami red zone, by implementing the UNESCO-IOC Tsunami Ready Community indicators. The project was driven by the urgent need to transform the community's fatalistic perception of disasters into a proactive and prepared mindset. The methodology employed a participatory approach through socialization, Focus Group Discussions, and community-led evacuation mapping, involving various local stakeholders such as the Disaster Preparedness Group and the Tsunami Ready Community forum. The results indicate a significant increase in disaster literacy, with participants' ability to identify early warning signs and evacuation routes rising from 35% to 85%. Furthermore, all 12 Tsunami Ready indicators were successfully addressed, including the development of participatory evacuation routes and the establishment of a localized early warning communication system. This program demonstrates that community-based disaster mitigation, supported by social capital and clear institutional coordination, is essential for building sustainable resilience in vulnerable coastal areas.